Representing communities : discourse and contexts - Sanz Sabido, Ruth (Palgrave Macmillan, 2020)
This edited collection offers the latest research into the reproduction of ‘hegemonic’ discourse and the ways in which the description and evaluation of social groups affects their ability to exercise cultural and political autonomy. The book examines the representations of a number of communities and social groups, both within their ‘micro-contexts’, and with reference to the economic, political, social, cultural and technological ‘macro-contexts’ in which they are embedded. The analysis highlights the connections between discourse, power, dominance and social inequality, focusing on patriarchal, capitalist and postcolonial representations and power imbalances. Based on a combination of theoretical and empirical analyses, the collection offers an array of macro-social critiques based on the analysis and critical understanding of contemporary contexts and representations, and how they contribute to political, social, economic and cultural practicesIntroduction: communities, discourse and contexts / Ruth Sanz Sabido -- Constructing community: notes on a slippery concept / Rinella Cere -- Transforming the politics of gender and voice: strategies of expertise and experience / Anita Biressi and Heather Nunn -- Populism, "community" and political culture: the revenge of the liberal elite / Stuart Price -- Discursive colonialism: German settler communities, their media and infrastructure in Africa, 1898-1914 / Corinna Schäfer -- Legitimising political homophobia: sexual minorities and Russian television news / Anna Khlusova -- Interrogating representations and misrepresentations of violence: the contested identities of generation 1.5 Somalis in Melbourne / Elizabeth Lakey -- New coverage of a women's hunger strike against "chauvinist violence" / Ruth Sanz Sabido -- Egresses: countering stereotypes of blackness and disability through Horrorcore and Krip Hop / Mikko O. Koivisto -- New Orleans, food, race and gender on television: Frank's Place and Treme / Robin Roberts -- Partiality, patriotism and propaganda: aggregating local news sources in Ukraine / Richard Pendry -- Constructing "ordinary people" on British television: notes on the politics of representation / Rosalind Brunt